Sustainable Urban Park: A Case Studies of Taman Awam Teluk Likas, Kota Kinabalu, Sabah. Malaysia - Normah Abdul Latip; Mohd Umzarulazijo Umar; Mohamad Pirdaus Yusoh; Kasim Mansur; Ang, Kean Hua; Rosazman Hussin; Dayang Siti Noorafidah Datu Nordin (Malaysia Institute of Planners, 2023)
Urban Park is a manifest of healthy images surrounding the city and indicating policy the local authority implements. The studies purposely to measures the level of satisfaction in visitors toward the current condition of the study area as an urban recreational park. A descriptive research approach was used on 187 respondents in the study area. A Satisfaction Index Analysis (SIA) was imposed to see the level of visitor satisfaction with the environment, facilities and amenities provided. Preliminaries’ finding indicates that most respondents were satisfied with the facilities and amenities provided in the study area. Whereby for the SIA analysis from 29 variables, info signage with 0.9401 (excellence) is the highest, and oppositely the lowest is debris collection centre at 0.6086 (fair). The finding demonstrates that the local authority's facilities and amenities are sustained towards visitors to the area.